A reply to: Chorzów Factory – intellectual property and the continuity of international law in investor-state dispute settlement. Issue 4 (December 2021) - Ferguson*, Alexander
Abstract : The case involving the nitrate factory at Chorzów, Upper Silesia has been the subject of much academic commentary. Last year the intellectual property aspects of the case were explored in this journal. In this reply, I express doubts about whether the case involved the expropriation of intellectual property rights (IPRs) for two reasons. First, there are grounds to question the existence of IPRs. Second, even if there were IPRs, the Permanent Court of International Justice does not appear to have found that IPRs were taken. Instead, the case serves as a reminder of the importance of identifying the legal status of an IPR in the relevant territory when seeking to protect it under international law. * My thanks to Martyna Mielniczuk-Skibicka and Kacper Górniak. All errors are my own.